Calorimetric study of cowpea protein isolates: effect of calcium and high hydrostatic pressure - Peyrano, Felicitas (2017)
The thermal properties of cowpea protein isolates (CPI) were studied by differential scanning calorimetry under the influence of various conditions. An increase in the pH of protein extraction, from 8.0 to 10.0, during CPI preparation promoted a partial denaturation of cowpea proteins. Increases in enthalpy change of denaturation (ΔH) and temperature of denaturation (Td) were detected with increasing protein concentration from 7.5 to 10.5% (w/w). This behavior suggests that denaturation involves a first step of dissociation of protein aggregates. Calcium induced thermal stabilization in cowpea proteins, the increase in Td was ca. 0.3 °C/mM for protein dispersions of 7.5% (w/w) for 0 to 40 mM CaCl2. High hydrostatic pressure (HHP) induced denaturation in CPI in a pressure level dependent manner. The presence of calcium protected cowpea proteins towards HHP-induced denaturation when pressure level was 400 MPa, but not when it was 600 MPa. Thermal properties of cowpea protein isolates were very sensitive to processing conditions, these behaviors would have implications in processing of CPI-containing foodstuff.